Effect of think-pair-share instructional strategy on senior secondary school students' academic achievement in mathematics in Ogun State - Badru, Ademola Kehinde (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2025)
This study investigated the effect of the Think-Pair-Share instructional strategy on senior secondary school students' achievement in mathematics in Ogun state, Nigeria.  The study adopted a pre-test, post-test, and control group quasi-experimental research design with a 2X3X2 factorial matrix. The sample comprised 104 students from two classes of the SS2 students. Two instruments used were the Mathematics Achievement Test (MAT) and Instructional treatment packages (experimental and control). Data was analysed with descriptive and inferential statistics (Analysis of Covariance) to test hypotheses 0.05 significance level. The result showed a significant main effect of treatment and parental educational background on students' academic achievement in Mathematics (F (1,103) = 13.092; F (2,103) = 15.327 respectively, P < 0.05). It showed that students taught with the Think-Pair-Share instructional strategy recorded a higher adjusted post-test mean score in MAT (21.91). However, the outcomes of treatment and Parental education background levels contributed 35.4% and 39.5%, respectively, to the variance in students' achievement in mathematics. It is concluded that this strategy encourages students to participate actively and interact, thereby making them take responsibility for their learning. As part of the recommendations, mathematics teachers should be encouraged to use the think-pair-share instructional strategy as a variety tool in mathematics classrooms. Penelitian ini menyelidiki pengaruh strategi pembelajaran Think-Pair-Share terhadap prestasi siswa sekolah menengah atas dalam bidang matematika di negara bagian Ogun, Nigeria. Penelitian ini menggunakan desain penelitian kuasi-eksperimental pre-test, post-test, dan kelompok kontrol dengan matriks faktorial 2X3X2. Sampel terdiri dari 104 siswa dari dua kelas siswa SS2. Dua instrumen yang digunakan adalah Tes Prestasi Matematika (MAT) dan paket perlakuan instruksional (eksperimen dan kontrol). Data dianalisis dengan statistik deskriptif dan inferensial (Analisis Kovarians) untuk menguji hipotesis pada tingkat signifikansi 0,05. Hasil penelitian menunjukkan adanya efek utama yang signifikan dari perlakuan dan latar belakang pendidikan orang tua terhadap prestasi akademik siswa di bidang Matematika (F (1.103) = 13.092; F (2.103) = 15.327, P < 0.05). Hasil penelitian menunjukkan bahwa siswa yang diajar dengan strategi pembelajaran Think-Pair-Share mencatat nilai rata-rata post-test yang lebih tinggi dalam MAT (21,91). Namun, hasil dari perlakuan dan tingkat latar belakang pendidikan orang tua masing-masing berkontribusi sebesar 35,4% dan 39,5% terhadap varians pencapaian siswa dalam matematika. Dapat disimpulkan bahwa strategi ini mendorong siswa untuk berpartisipasi aktif dan berinteraksi, sehingga membuat mereka bertanggung jawab atas pembelajaran mereka. Sebagai bagian dari rekomendasi, guru matematika harus didorong untuk menggunakan strategi pembelajaran think-pair-share sebagai alat variasi di kelas matematika.